Development of Web-Based Learning Media on Hindu-Buddhist History Materials for Tenth-Grade Students at SMA Negeri 7 Semarang - Demas, Arvin Satya; Atno, Atno (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
This study aims to develop web-based learning media for the topic of Hindu-Buddhist kingdoms in history subjects for tenth-grade students at SMA Negeri 7 Semarang. The background of this research lies in the absence of web-based learning media applied in the history learning process, particularly for the topic of Hindu-Buddhist kingdoms. History teachers also expressed the need for innovative media that can support teaching and learning activities in a more interactive and flexible manner. This study employed a Research and Development (R&D) method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The product developed is a web-based learning platform accessible online, containing instructional materials, educational videos, and practice questions. This media is expected to serve as a solution to improve the quality of history education in schools.